Strategies, policies, and directions for refugee education - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2018)
This volume examines how Governmental agencies, non-profit organizations and educational institutions are mobilizing their resources to promote inclusion of refugees and internally displaced people. It explores the grass root campaigns that are working towards participation and full involvement for disadvantaged groups, and towards equitable distribution of opportunities in both home and host countries. The case studies included emphasize the importance of effective cooperation and coordination across multi-sectoral responses, and the need to take into account the social and economic dimensions of inclusion. Providing educators at all levels with a research and evidence based understanding of the educational opportunities and challenges facing refugees (both children and adults), this important book considers related and overlapping issues such as equality, equity, power, privilege, identity, rights, and pluralism, and addresses the relevant issues at the theory, policy, and practice levels.